Assessment of participatory management of irrigation schemes in Sri Lanka: partial reforms, partial benefits - Samad, M.; Vermillion, Douglas L. (International Water Management Institute, 1999)
Describes the application of a standard methodology developed by IWMI to assess the impact of irrigation management transfer on the performance of irrigation schemes. Includes detailed analysis of the effects of participatory management on the performance of irrigation schemes in Sri Lanka.